Computational modelling of phospholipids in plasma membranes - Lanai, Victor (My University, 2022)
The purpose of this project was to investigate if the constituents of phospholipids in plasma membranes affect how cells interact with graphene (G) and graphene oxide (GO). It has previously been shown that vertically grown graphene flakes are effective in killing bacteria whilst keeping mammalian cells intact. However, the mechanism behind this phenomena is not known, and is at the same time difficult to measure experimentally. Therefore we choose density functional theory as a tool, with the goal to enhance the understanding. This thesis dives into the plasma membranes of bacterial and mammalian cells, and target different phospholipids in these membranes. The project started off by creation of a library of single phospholipids. These were put together into systems of pairs for calculation of bonding between different phospholipids. Further, both a G and a GO flake were created, and incorporated into the systems with the phospholipid pairs. Analysis of the interaction energies between these flakes with the phospholipid pairs was performed, both when the flakes approach the phospholipids, and upon penetration of the membrane. Calculations show that the most abundant phospholipids in mammalian cells have stronger bonding to each other, compared to bacterial phospholipids. Further, when the G/GO flakes enter between the phospholipid pairs, the bacterial pair exhibits less repulsive interactions, and a more stable system with the flakes were found. Therefore, these variables may contribute to the diverse robustness between bacterial and mammalian cells, and thus, the composition of phospholipids can be an important factor in explaining the difference in viability between organisms.
Keywords: Density Functional Theory, Microorganism, Bacteria, Eukaryotes, Mammalian, Graphene, Graphene oxide